PENGGUNAAN KARTU BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Imas imas; Titim Kurnia (JENTRE, 2021)
The research is based on the poor reading ability of Indonesian students. To improve reading skills, it must be developed from elementary school as the foundation for the next level of education. In this regard, the researcher collaborated with colleagues to research early reading ability for the first grade of students at Ciwaruga 1 Elementary School, West Bandung Regency. Research subjects numbered 22 pupils. The method used is descriptive analysis with one shot case study technique. The researchers used several instruments to collect the data of student abilities as well as to examine word and picture cards effectiveness in the learning process of early reading. Based on data, there are several findings that the ability of early reading so far has only reached 45%. In addition, the effectiveness of using illustrated word and picture cards in early reading is 0.349, which exceeds the level of 0.05. Therefore, it can be interpreted that using illustrated cards has a very significant impact for improving early reading ability of students at the first grade.